A New Simulation Tool for Sensor Networks Based on an Energy-Efficient and Fault-Tolerant Methodology - Hanene Rouainia; Hanen Grichi; Laid Kahloul; Mohamed Khalgui (Springer, Cham, 2023)
Recently, reconfigurable wireless sensor networks (RWSNs) have attracted a lot of attention in research and industrial communities. They became more complex and dynamic systems which led to the emergence of many challenges. The lack of energy, real-time constraints, and software and hardware failures are the most important challenges in RWSNs. Indeed, several solutions have proposed to come up with these challenges. To avoid huge costs in terms of money, time, and effort of real experimentation, networks’ simulation tools have become an essential necessity to study the impact of the proposed solutions. In this work, we propose a new energy-efficient and fault-tolerant methodology that composed of a set of solutions summarized in the use of mobile sink nodes (MSNs), application of the mobility, resizing, and test packet technique using a multi-agent architecture and an energy-efficient routing protocol. Moreover, we propose a new discrete-event simulation tool named RWSNSim designed for sensor networks (WSNs & RWSNs). We present its description, modeling, and provided services. The proposed simulation tool allows simulating sensor networks with and without application of the proposed methodology. Finally, we simulate a case study using RWSNSim in a 3D environment which proves the effectiveness of the proposed methodology and demonstrate the efficiency of the suggested simulation tool.